The Prognostic Value of Combined Systemic Immune-Inflammatory Index (SII) and Prognostic Nutritional Index (PNI) in Solid Tumor - Zhang Y; Tang M; Gu QH; Zhou LN; Chen MB (Cancer Management and Research, 2025)
Yan Zhang, Min Tang, Qian-Hui Gu, Li-Na Zhou, Min-Bin Chen Department of Oncology & Radiotherapy, Affiliated Kunshan Hospital of Jiangsu University, Kunshan, Jiangsu, 215300, People’s Republic of ChinaCorrespondence: Min-Bin Chen, Department of Oncology & Radiotherapy, Affiliated Kunshan Hospital of Jiangsu University, Kunshan, Jiangsu, 215300, People’s Republic of China, Email cmb1981@163.comBackground: Inflammation and nutrition status were the essential factors for cancer initiation and progression. Previous studies have confirmed systemic immune-inflammatory index (SII) and prognostic nutritional index (PNI) could predict the prognosis of cancer patients. The aim of this study was to evaluate the pre-treatment SII and PNI in predicting outcomes in different cancers.Methods: The retrospective study included 508 cancer cases diagnosed between June 2013 and June 2022. The pre-treatment SII and PNI were calculated from peripheral blood samples, and the cutoff value was determined by receiver operating characteristic (ROC). The association of SII, PNI with clinicopathological characters and prognosis were assessed by Cox regression and Kaplan–Meier methods.Results: The ideal preoperative SII and PNI cutoff values were 792.0 and 49.825, respectively. High SII group as well as low PNI group had worse prognosis. Patients satisfied both high SII and low PNI had the lowest overall survival (OS) rate (p < 0.001). Multivariable Cox regression analysis identified that the tumor stage (p < 0.001), BMI (p = 0.042), SII (p = 0.001) and AGR (p = 0.047) were independently prognostic markers for OS.Conclusion: High level of pretreatment SII may be an independent prognostic factor for cancer patients. Patients with both high SII and low PNI had the worst prognosis.Keywords: systemic immune-inflammatory index, prognostic nutritional index, prognosis, solid tumor